USE OF PRACTICAL-ORIENTED APPROACH IN VOCATIONAL TRAINING FUTURE TEACHERS - Palshkova, I.O. (Pedagogy of Higher and Secondary Education, 2004)
The article shows the using of practical-oriented approach in professional training of future teachers.